2014
DOI: 10.1111/vox.12196
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and mechanistic evaluation for the weak A phenotype in Ael blood type with IVS6 + 5G>A ABO gene mutation

Abstract: This study demonstrates that aberrant splicing of A transcripts contributes to weak A expression and the weak agglutination of Ael -RBCs, adding to the complexity for the regulatory mechanisms of ABO gene expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 26 publications
0
5
0
1
Order By: Relevance
“…Clinically, subtype A is divided into A1, A2, A3, Ax, Aend, Am and Ael according to decreasing number of A antigens [10], among which Ael subtype contains the least number of A antigen on the red blood cells. The reactivity of Ael red blood cells can be detected only by absorption‐elution experiments, and its serum does not agglutinate or weakly agglutinate with type A red blood cells, that is, A elution type [11–13].…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, subtype A is divided into A1, A2, A3, Ax, Aend, Am and Ael according to decreasing number of A antigens [10], among which Ael subtype contains the least number of A antigen on the red blood cells. The reactivity of Ael red blood cells can be detected only by absorption‐elution experiments, and its serum does not agglutinate or weakly agglutinate with type A red blood cells, that is, A elution type [11–13].…”
Section: Discussionmentioning
confidence: 99%
“…Some variations in the splice sites of the ABO gene are associated with some ABO subtypes. Chen DP et al reported c.155 + 5G > A (IVS3 + 5G > A) in a B3 individual and c.374 + 5G > A (IVS6 + 5G > A) in an Ael individual 31 , 32 . In theory, changes in the ABO gene splice site result in the formation of new RNA splice sites and therefore novel versions of ABO mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple ABO mRNA forms were detected in the normal ABO phenotype by RT–PCR, the majority of which lacked exon 6 [ 34 , 35 ]. However, in some individuals with ABO subtypes, RNA splicing of the ABO gene was detected [ 31 , 32 , 36 , 37 ]. An ABO* A1-like allele with a 4 bp deletion (c.236-239delCGTG) in exon 5 and a 20 bp downstream deletion in intron 5 affected the donor splice site [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Многообразие аллельных вариантов антигена А обусловлено либо миссенсмутациями в гене АВО*А (точечными заменами нуклеотидов в кодирующей ча сти гена АВО*А, ведущими к замене аминокислоты в соответствующем белковом продукте) либо сплай синговыми мутациями (затрагивающими сайты сплай синга или создающими новые сайты сплайсинга в инт ронных областях гена, что сопровождается либо делецией смежного с мутацией экзона, либо наруше нием удаления соответствующего интрона при про цессинге первичного РНКтранскрипта). Многие сплайсинговые мутации приводят к сдвигу рамки счи тывания или к формированию стопкодона, что при водит к синтезу функционально неактивной Аглико зилтрансферазы [3].…”
Section: Discussionunclassified